An Allosteric-Probe for Detection of Alkaline Phosphatase Activity and Its Application in Immunoassay - Guo, Jingjing; Gao, Mingxuan; Song, Yanling; Lin, Li; Zhao, Kaifeng; Tian, Tian; Liu, Dan; Zhu, Zhi; Yang, Chaoyong James (Frontiers in Chemistry, 2018)
A fluorescence strategy for alkaline phosphatase (ALP) assay in complicated samples with high sensitivity and strong stability is developed based on an allosteric probe (AP). This probe consists of two DNA strands, a streptavidin (SA) aptamer labeled by fluorophore and its totally complementary DNA (cDNA) with a phosphate group on the 5’ end. Upon ALP introduction, the phosphate group on the cDNA is hydrolyzed, leaving the unhydrolyzed cDNA sequence for lambda exonuclease (λ exo) digestion and releasing SA aptamer for binding to SA beads, which results in fluorescence enhancement of SA beads that can be detected by flow cytometry or microscopy. We have achieved a detection limit of 0.012 U/mL with a detection range of 0.02~0.15 U/mL in buffer and human serum. These figures of merit are better than or comparable to those of other methods. Because the fluorescence signal is localized on the beads, they can be separated to remove fluorescence background from complicated biological systems. Notably, the new strategy not only applies to ALP detection with simple design, easy operation, high sensitivity and good compatibility in complex solution, but also can be utilized in ALP-linked immunosorbent assays for the detection of a wide range of targets.